N. Allington and N. Thompson (eds.), English, Irish and Subversives Amongst the Dismal Scientists, 399pp. - Noel Thompson (Emerald, 2010)
This is a volume of essays on nineteenth century political economists who have suffered neglect by historians of economic thought. The book covers a very wide range of authors whose work and neglect is discussed by those with a particular knowledge of their work.